(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indigenous or Indigeneity has been often used in today’s contemporary debate. India being a diverse country has a very rich ethnic composition. Manipur which lies in the easternmost part of India has its shares of Diversity. Manipur boast of having different ethnic communities, majority of them being the Meitei, Kuki’s and the Naga’s, having rich culture and tradition unique to each other. The present paper highlights the indigenous practice of brewing beverages among Meitei communities of Kakching district. The practice of brewing has been an inherent part of their culture since time immemorial and very much in practice till modern day today. The findings of the study also show that it has been one of the main sources of livelihood. The paper becomes more interesting as it highlights the legal aspects of brewing as well.